1987
DOI: 10.1111/j.1365-2672.1987.tb02669.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds produced by meat pseudomonads and related reference strains during growth on beef stored in air at chill temperatures

Abstract: Volatile compounds produced by 31 strains of pseudomonads and by reference strains of Pseudomonas fragi and Ps. fluorescens biotype 1 during growth on beef stored at 6 degrees C in air were analysed by gas chromatography-mass spectrometry of headspace gases. Compounds of major sensory significance were ethyl and methyl esters of C2-C8 fatty acids and sulphur-containing compounds which included methane- and isopropanethiols and their related sulphides and thioesters but not hydrogen sulphide. Ester production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 25 publications
(35 reference statements)
2
30
0
3
Order By: Relevance
“…Only a few esters were found in the meat samples inoculated with P. fragi 25P, although several studies report on the esters as the major volatile compounds produced by P. fragi in spoiling foods (8,13,45). However, Edwards et al (13) evidenced that not all of the strains of P. fragi that they used to spoil meat at a chill temperature were able to produce esters. In addition, when six different species of Pseudomonas were screened for their activity in cheese, it was shown that the production of volatile compounds is species dependent (46).…”
Section: Discussionmentioning
confidence: 92%
“…Only a few esters were found in the meat samples inoculated with P. fragi 25P, although several studies report on the esters as the major volatile compounds produced by P. fragi in spoiling foods (8,13,45). However, Edwards et al (13) evidenced that not all of the strains of P. fragi that they used to spoil meat at a chill temperature were able to produce esters. In addition, when six different species of Pseudomonas were screened for their activity in cheese, it was shown that the production of volatile compounds is species dependent (46).…”
Section: Discussionmentioning
confidence: 92%
“…Many peaks in the mass spectra could be tentatively identified with typical and wellknown spoilage compounds (1,2,4,5,7,13,20). A few of those components which are relevant for this work (high correlation with bacterial numbers) are listed in Table 2, which also gives the protonated mass (mϩ1), the chemical formula, and a reference where this spoilage compound was identified.…”
Section: Microbiological Analysismentioning
confidence: 99%
“…A vast literature on spoilage compounds in meat exists (1,2,4,5,7,13,20). This allows a first assignment of the prominent ion peaks.…”
Section: Preparation Of Meatmentioning
confidence: 99%
“…The occurrence of psychrotrophic bacteria in sausage may be attributed to the exposure of meat to different sources of microbial contamination including contact with hide, viscera, hands and clothing of personnel, water used for washing carcasses and equipment, and even air in the processing and storage areas The relatively high Pseudomonas and Aeromonas counts may be attributed to storage of meat for long time at room temperature during the manufacture [3, 281. However, such organisms utilize a variety of non-carbohydrate carbon compounds in food, producing a variety of products that affect flavour of food [8,12]. Some of these organisms are pathogenic to man, producing necrotic and ulcerative lesions in the alimentary tract [20, 251.…”
Section: Discussionmentioning
confidence: 99%